Prehospital cardiopulmonary resuscitation with manual or mechanical chest compression: A study of compression‐induced injuries. Issue 6 (18th March 2019) - Milling, Louise; Astrup, Birgitte Schmidt; Mikkelsen, Søren
Abstract : Objective: Concerns for iatrogenic injuries associated with cardiopulmonary resuscitation led us to investigate the extent and the pattern of chest compression‐related injuries in patients subjected to either mechanical and/or manual cardiac compression. Method: In a retrospective study, we performed a manual review of all prehospital discharge reports, in‐hospital records, and autopsy reports for evidence of injuries related to chest compression. We included all patients receiving physician‐administrated treatment for out‐of‐hospital cardiac arrest in the Region of Southern Denmark from 2015 to 2017. Results: Eighty four patients undergoing manual and mechanical chest compression and 353 patients with manual chest compression only were included. Unadjusted, mechanical chest compression as an adjunct was associated with a higher risk of injuries than manual chest compression ( P < 0.001, odds ratio, OR 3.10). Adjusted for the duration of compression, this difference waned. Visceral injuries were more frequent in patients receiving mechanical chest compression even when adjusted for the duration of compression, age, sex, body mass index and anticoagulant therapy ( P < 0.001, OR 29.84). We found a higher incidence of potentially life‐threatening injuries in patients receiving mechanical chest compression. The occurrence of injuries overall was associated with the duration of chest compression ( P = 0.02, OR 1.02). Conclusion: Mechanical chest compression as an adjunct to manual chest compression was strongly associated with potentially life‐threatening visceral injuries. The duration of chest compression was associated with injury. Our results suggest that mechanical chest compression should only be applied in situations where manual chest compression is unfeasible.